2020
DOI: 10.1159/000508306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Evaluation after Adopting Contingent Cell-Free DNA Screening for Fetal Trisomies in South Spain

Abstract: <b><i>Introduction:</i></b> Contingent cell-free (cf) DNA screening on the basis of the first-trimester combined test (FCT) results has emerged as a cost-effective strategy for screening of trisomy 21 (T21). <b><i>Objectives:</i></b> To assess performance, patients’ uptake, and cost of contingent cfDNA screening and to compare them with those of the established FCT. <b><i>Methods:</i></b> This is a prospective cohort study including all si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Contingent screening, i.e., performing cfDNA only in those patients with high risk in the combined test, has shown to be a cost-effective way to enhance first-trimester combined test [5, 6, 8]; however, the difficulty lies in setting the cut-off threshold to consider the patient to be at increased risk to perform cfDNA test, since, depending on it, both the detection rate and the number of patients to be included in the program vary, and therefore the costs are also different. Gil et al [9] reported detection rates depending on the cut-off chosen for contingent screening: to achieve 100% detection of T21s, the cut-off point should be higher than 1:3,500.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contingent screening, i.e., performing cfDNA only in those patients with high risk in the combined test, has shown to be a cost-effective way to enhance first-trimester combined test [5, 6, 8]; however, the difficulty lies in setting the cut-off threshold to consider the patient to be at increased risk to perform cfDNA test, since, depending on it, both the detection rate and the number of patients to be included in the program vary, and therefore the costs are also different. Gil et al [9] reported detection rates depending on the cut-off chosen for contingent screening: to achieve 100% detection of T21s, the cut-off point should be higher than 1:3,500.…”
Section: Discussionmentioning
confidence: 99%
“…This is the main reason why it has not been widely implemented to be used as universal first-trimester screening in national health programs, as this strategy has proven not to be cost effective [4]. In contrast, several studies have shown that contingent screening, i.e., the implementation of combined screening with cfDNA testing in at-risk populations, is a cost-effective strategy, and in fact, this is the trend that major health systems are focusing on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, its expensive costs have put a toll on its implementation as a universal screening. Several authors have evaluated various contingent screening strategies using different cut-off points for the high-risk group [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is recommended to perform universal screening with the FCT, followed by a contingent cfDNA test for those with an intermediate risk between 1/50 and 1/250, at the time of the blood sampling, or 1/270 at the time of the delivery, and only those with a high-risk FCT above 1/50 are offered an IT [ 5 ]. This strategy allows us to maintain the DR [ 11 , 14 ] without increasing the economic costs [ 15 ]. However, it has been described that most aneuploidies are within the group of patients with a risk above 1/10 or with an increased thickness of the NT [ 13 ].…”
Section: Introductionmentioning
confidence: 99%